Lanreotide autogel/depot in advanced enteropancreatic neuroendocrine tumours: final results of the CLARINET open-label extension study - Caplin, Martyn E; Pavel, Marianne; Phan, Alexandria T; Ćwikła, Jarosław B; Sedláčková, Eva; Thanh, Xuan-Mai Truong; Wolin, Edward M; Ruszniewski, Philippe; CLARINET Investigators (Endocrine, 2021)
PURPOSE: In the phase III CLARINET study (NCT00353496), lanreotide autogel/depot (lanreotide) significantly improved progression-free survival (PFS) vs placebo in patients with non-functioning intestinal or pancreatic neuroendocrine tumours (NETs). The aim of CLARINET open-label extension (OLE) (NCT00842348) was to evaluate long-term safety and efficacy of lanreotide in these patients. METHODS: Patients from the CLARINET study were eligible for the OLE if they had stable disease (irrespective of treatment group) or progressive disease (PD) (placebo-treated patients only). All patients in the OLE received lanreotide 120 mg every 28 days. Computed tomography or magnetic resonance imaging scans were conducted every 6 months and assessed locally for PD (the final scan was also assessed centrally). RESULTS: Overall, 89 patients took part in the OLE (lanreotide, n = 42; placebo, n = 47). Median (range) exposure to lanreotide in patients who received lanreotide in the core study and OLE (LAN-LAN group) was 59.0 (26.0-102.3) months. In this group, the overall incidences of adverse events (AEs) and treatment-related AEs were lower in the OLE than in the core study. Median [95% CI] PFS in the LAN-LAN group was 38.5 [30.9; 59.4] months. In placebo-treated patients with PD at the end of the core study, time to death or subsequent PD during the OLE was 19 [10.1; 26.7] months. CONCLUSIONS: This study provides new evidence on the long-term safety profile and sustained anti-tumour effects of lanreotide autogel/depot in indolent and progressive metastatic intestinal or pancreatic NETs.
Keywords: Humans; Safety; Pancreatic Neoplasms; nádory slinivky břišní; Somatostatin; Progression-free survival; cyklické peptidy; lidé; neuroendokrinní nádory; Antineoplastic Agents; Neuroendocrine tumours; protinádorové látky; Neuroendocrine Tumors; Lanreotide depot; Lanreotide autogel; Peptides, Cyclic; somatostatin